Research Progress in the Study of Traditional Chinese Herbal Medicine Extracts Regulating Ferroptosis thus Improving the Symptom of Alzheimer's Disease - PEI Jinying, SONG Jinzhou, MA Daofeng, LUO Xiaoting, LIU Bin, DONG Xiaohong, CONG Shuyuan (Zhongguo quanke yixue)
Alzheimer's disease (AD) is a common neurodegenerative disease in the elderly population. It's typical clinical manifestation is progressive memory impairment. Ferroptosis, rising as a new research direction on AD biological mechanism in recent years, mainly studies on iron-dependent programmed cell death. A large amount of evidence has shown that AD is closely related to ferroptosis in the brain. However, the exact mechanism of the role ferroptosis has played in AD is still unclear. One of the most popular research results indicates that AD might be induced by iron metabolism disorders, lipid peroxidation, and amino acid metabolism, thereby affecting the deposition of iron ions in the brain. So far, some effective chemical components of traditional Chinese herbs as cures of AD have been studied in depth, such as rhodiola rosea, polygala root, ginkgo biloba, poria cocos, etc. These traditional Chinese herbs have shown remarkable effects in the treatment of AD by means of targeting ferroptosis. In this context, this review systematically elaborates on the metabolism of iron in the brain, the characteristics of ferroptosis, and focuses on the metabolic regulation mechanism of ferroptosis. Meanwhile, this review also discusses the connection between ferroptosis and AD. Furthermore, it lists the effective compositions in traditional Chinese herbs that can improve AD by inhibiting ferroptosis, so as to provide reference information for the development and research of ferroptosis inhibitors in the future.